A feasibility study on establishing an eco-brick business as a supplier of sustainable construction materials - Jeremy Ira R. Amarante, Kiara Marie M. Brillo, Meriam R. Dilangalen, Juliah Neil G. Pama, Irene Mae O. Porras, Glen Mark C. Ramos, Rowena T. Terrenal, Sophia Margareth S. Tonido, Karen M. Zambrana. 4 0 16; 5
u
Feasibility Study: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2